Structure of natural gas markets in Argentina and antitrust issues in regional energy integration - Bondorevsky, Diego (IDB WashingtonUS, 2001)
Examines the infrastructure and performance of the natural gas market in Argentina. Looks at the effects that this sector has had on overall regional energy integration, and what regulatory and antitrust issues have arisen throughout the region as a consequence.